Literasi Pendidikan Antikorupsi dan Reformasi Birokrasi di Banten - Supriatno, Eko (Universitas Mathla'ul Anwar Banten, 2025)
Corruption is not merely a violation of the law, but also a moral crisis and a lack of public ethical literacy. In the Banten context, bureaucratic corruption remains a serious challenge to achieving clean and integrated governance. This study highlights the importance of anti-corruption educational literacy as a cultural instrument that fosters integrity awareness from an early age, as well as its relevance to bureaucratic reform oriented toward transparency and accountability. This approach emphasizes not only legal enforcement but also the transformation of the values and behaviors of civil servants through educational networks, government institutions, and civil society. By adopting a collaborative inter-organizational model, the corruption eradication strategy in Banten is directed at developing a sustainable integrity ecosystem. The results of this study indicate that anti-corruption educational literacy effectively drives a shift in bureaucratic culture from pseudo-compliance to moral awareness. Therefore, bureaucratic reform in Banten cannot be achieved solely through regulations but must be supported by education in the values and practices of integrity as the primary foundation of civilized governance.